Hypercalcemia: A complicated puzzle - Mara Carsote; Corina Chirita; Anda Dumitrascu; Florica Sandru; Claudia Mehedintu; Razvan Cosmin Petca; Mihai Cristian Dumitrascu (Romanian Medical Journal, 2021)
This is a mini-review concerning hypercalcemia of malignancy that represents a challenging condition requiring rapid management, not only in relationship with short term complications, but also with long term mortality concerning the originating tumor approach (if feasible). Hypercalcemia on a patient with previously known or unknown cancer may be caused by dehydration, concurrent medication causing increased serum calcium levels, concomitant primary or renal hyperparathyroidism, over production of vitamin D (which may be tumor-related) or by specific circumstances that induce suppression of parathormone (PTH), so called PTH-independent mechanisms. Specific circumstances related to an active cancer means an ectopic production of parathormone, metastasis causing osteolytic lesions, tumors that produce PTHrP (parathormone related peptide) and abnormal production of 1,25-dihydroxyvitamin D by a hematologic malignancy. Parathyroid carcinoma induces an excess of PTH which is caused by a malignancy but it is not a PTH independent entity. Once a malignancy-related hypercalcemia is identified based on biological panel (mostly blood assays), the investigations are essentially continued with different imaging techniques depending on signs (if any), accessibility, etc. The approach is based on a multidisciplinary panel, on one hand, in order to restore normal levels of calcium, on the other hand, to rapidly address the underlying cause. This is essential to contribute to the outcome which typically is poor.